Elevated occupational exposure to chlorinated phosphate esters at a construction materials manufacturing plant. (June 2020) - Shi, Fengqiong; Liang, Kang; Liu, Rui; Dong, Quanxiao; He, Zuoliang; Xu, Jinwen; Liu, Jingfu
Graphical abstract: Highlights: The first report on occupational exposure of OPEs during the OPE-related products manufacturing processes. Levels of TCEP and TCPP in factory dust were the highest reported hitherto. Levels of urinary BCEP for workers were several orders magnitude higher than previously reported occupational populations. OPEs (especially TCEP) exposures posed medium to high potential cancer risks on workers. Abstract: Background: Numerous studies have documented that the general population is widely exposed to organophosphate esters (OPEs), yet studies on the emissions of OPEs in the industrial application processes and their occupational exposure are scarce. The aim of this study was to assess the exposure to OPEs for workers engaged in OPE-retarded construction material manufacturing plant in China. Method: Paired dust samples (12 samples each time) from an OPEs retarded building materials manufacturing plant during the plant uptime and downtime have been analyzed for tris(2-chloroethyl)-phosphate (TCEP), tris(2-chloroisopropyl) phosphate (TCPP), and other commonly used OPEs. Moreover, nine OPEs metabolites (mOPEs) in urine samples (n = 42) from fourteen workers who engaged in this plant were also measured. The daily exposure doses to OPEs were estimated from the measured urinary concentrations of corresponding mOPEs. Results: Thirteen out of fourteen studied OPEs (except for tri-n-propyl phosphate, TnPP) were determined in all dust samples from the manufacturing plant, and TCEP and TCPP were the predominant compounds in dust collected from the plant uptime and downtime. Overall, the occupationally exposed population had significantly higher (p < 0.01) urinary levels of mOPE, especially for bis (2-chloroethyl) phosphate (BCEP), relative to the reference population. Workshop workers who directly involved in the production of OPEs treated products had higher OPEs exposure. Risk assessment revealed that cancer risk (1.5 × 10 −6 –8.5 × 10 −4 ) for all workers was larger than 1 × 10 −6 when levels of mOPEs in urine from workers were used for estimating OPEs exposure, revealing moderate to high potential cancer risk to workers from OPEs exposure. Conclusion: To our knowledge, this is the first study reporting emissions of OPEs in OPE-treated products manufacturing processes and the potential exposure of the occupationally exposed population. OPEs, especially for TCEP and TCPP, present at elevated levels and pose moderate to high potential health risks to the exposed workers, emphasizing the importance of strengthening occupational exposure prevention in similar industries.